2014
DOI: 10.1016/j.crvi.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of ant communities and indicator species analysis using self-organizing maps

Abstract: To understand the complex relationships that exist between ant assemblages and their habitats, we performed a self-organizing map (SOM) analysis to clarify the interactions among ant diversity, spatial distribution, and land use types in Fukuoka City, Japan. A total of 52 species from 12 study sites with nine land use types were collected from 1998 to 2012. A SOM was used to classify the collected data into three clusters based on the similarities between the ant communities. Consequently, each cluster reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The SOM (Kohonen, ), a heuristic model used for exploring and representing the linear and nonlinear relationships in high‐dimensional data sets, has also been used to characterize different patterns of communities (Céréghino et al ., ; Chon, and papers cited therein), but rarely in studies on terrestrial ecosystems (Groc et al ., ; Delabie et al ., ; Park et al ., ). This technique uses an array of prototype vectors that analyze the variance structure of the data set and converts relationships between the data into graphical representations in two dimensions.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The SOM (Kohonen, ), a heuristic model used for exploring and representing the linear and nonlinear relationships in high‐dimensional data sets, has also been used to characterize different patterns of communities (Céréghino et al ., ; Chon, and papers cited therein), but rarely in studies on terrestrial ecosystems (Groc et al ., ; Delabie et al ., ; Park et al ., ). This technique uses an array of prototype vectors that analyze the variance structure of the data set and converts relationships between the data into graphical representations in two dimensions.…”
Section: Methodsmentioning
confidence: 97%
“…Because most ant species have sedentary colonies, they are sensitive to changes in the environment and so have been used as indicators of these changes (Park et al ., ). For arboreal ants, the changes correspond to different tree sizes (ontogenic succession of TDAs as the trees grow; Dejean et al ., ) and to the different tree species related to the succession process leading to climactic forests (for the succession in Africa, see White, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The occurrence probability for each ant species in a given area is represented on the SOM map in gray scale, allowing us to analyze the effect of each species on the patterning input dataset (trees). A detailed description of the SOM is provided in Appendix S2 (BElectronic Supplementary Material^; for the ant distribution, see Park et al 2003Park et al , 2014Dejean et al 2015).…”
Section: Statistical Comparisonsmentioning
confidence: 99%
“…The five most abundant species in this study are also the most common ant species observed in the study area during spring to autumn (Ogata et al, 1998;Park et al, 2014aPark et al, , 2014b. The number of ant species observed at each study site represented ca.…”
Section: Resultsmentioning
confidence: 50%